Diversity and Assembling Processes of Bacterial Communities in Cryoconite Holes of a Karakoram Glacier - AMBROSINI, ROBERTO; MINORA, UMBERTO FILIPPO; R.S. Azzoni; G. Diolaiuti; C. Smiraglia; F. Musitelli; F. Navarra; I. Tagliaferri; I. Gandolfi; G. Bestetti; C. Mayer; A. Franzetti (Microbial Ecology, 2016)
Cryoconite holes are small ponds that form on the surface of glaciers that contain a dark debris, the cryoconite, at the bottom and host active ecological communities. Differences in the structure of bacterial communities have been documented among Arctic and mountain glaciers, and among glaciers in different areas of the world. In this study, we investigated the structure of bacterial communities of cryoconite holes of Baltoro Glacier, a large (62 km in length and 524 km2 of surface) glacier of the Karakoram, by high-throughput sequencing of the V5-V6 hypervariable regions of the 16S rRNA gene. We found that Betaproteobacteria dominated bacterial communities, with large abundance of genera Polaromonas, probably thanks to its highly versatile metabolism, and Limnohabitans, which may have been favoured by the presence of supraglacial lakes in the area where cryoconite holes were sampled. Variation in bacterial communities among different sampling areas of the glacier could be explained by divergent selective processes driven by variation in environmental conditions, particularly pH, which was the only environmental variable that significantly affected the structure of bacterial communities. This variability may be due to both temporal and spatial patterns of variation in environmental conditions.